An Electric‐Field‐Reinforced Hydrophobic Cationic Sieve Lowers the Concentration Threshold of Water‐In‐Salt Electrolytes (Adv. Mater. 47/2022). Issue 47 (24th November 2022) - Zhou, Anxing; Zhang, Jinkai; Chen, Ming; Yue, Jinming; Lv, Tianshi; Liu, Binghang; Zhu, Xiangzhen; Qin, Kun; Feng, Guang; Suo, Liumin
Abstract : Aqueous Battery Chemistry In article number 2207040, Guang Feng, Liumin Suo, and co‐workers report that when a small number of hydrophobic cations are introduced to an appropriate concentration electrolyte (ACE), the added cations can form an electric‐field‐reinforced hydrophobic cationic sieve (HCS) that blocks water away from the anode. As a result, ALIBs with HCS‐ACE can achieve lower costs and better performance.